Peptide nucleic acid (PNA) probe, kit and procedure for specific detection of Helicobacter pylori and applications thereof - Azevedo, N. F. (2008)
The current invention relates to the development of a peptide nucleic acid (PNA) probe for the specific detection of Helicobacter pylori. These probes are used in a process based on molecular biology techniques, namely the fluorescence in situ hybridization (FISH), and can be applied in a variety of samples such as biopsies, blood, air, food, water and other environmental samples. Due to the physical and chemical characteristics inherent to their structure, these probes are able to provide a more rapid and sensitive analysis than the DNA probes. Another aspect of the current invention is the development of a kit, based on the PNA probe and the FISH process, for the detection and/or quantification of the H. pylori in biological, clinic and/or environmental samples.